The ΔfbpAΔsapM candidate vaccine derived from Mycobacterium tuberculosis H37Rv is markedly immunogenic in macrophages and induces robust immunity to tuberculosis in mice - Mishra, Abhishek; Khan, Arshad; Singh, Vipul Kumar; Glyde, Emily; Saikolappan, Sankaralingam; Garnica, Omar; Das, Kishore; Veerapandian, Raja; Dhandayuthapani, Subramanian; Jagannath, Chinnaswamy (Frontiers in Immunology, 2024)
Tuberculosis (TB) remains a significant global health challenge, with approximately 1.5 million deaths per year. The Bacillus Calmette-Guérin (BCG) vaccine against TB is used in infants but shows variable protection. Here, we introduce a novel approach using a double gene knockout mutant (DKO) from wild-type Mycobacterium tuberculosis (Mtb) targeting fbpA and sapM genes. DKO exhibited enhanced anti-TB gene expression in mouse antigen-presenting cells, activating autophagy and inflammasomes. This heightened immune response improved ex vivo antigen presentation to T cells. Subcutaneous vaccination with DKO led to increased protection against TB in wild-type C57Bl/6 mice, surpassing the protection observed in caspase 1/11-deficient C57Bl/6 mice and highlighting the critical role of inflammasomes in TB protection. The DKO vaccine also generated stronger and longer-lasting protection than the BCG vaccine in C57Bl/6 mice, expanding both CD62L-CCR7-CD44+/-CD127+ effector T cells and CD62L+CCR7+/-CD44+CD127+ central memory T cells. These immune responses correlated with a substantial ≥ 1.7-log10 reduction in Mtb lung burden. The DKO vaccine represents a promising new approach for TB immunization that mediates protection through autophagy and inflammasome pathways.